The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/f10111020
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Trichoderma Fungi on the Tunneling, Aggregation, and Colony-Initiation Preferences of Black-Winged Subterranean Termites, Odontotermes formosanus (Blattodea: Termitidae)

Abstract: The black-winged subterranean termite, Odontotermes formosanus Shiraki, is a severe pest of plantations and forests in China. This termite cultures symbiotic Termitomyces in the fungal combs, which are challenged by antagonistic microbes such as Trichoderma fungi. In a previous study we showed that O. formosanus workers made significantly fewer tunnels in sand containing commercially formulated conidia of Trichoderma viride Pers. ex Fries compared with untreated sand. Herein, we hypothesize that fungi in the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…In addition, previous studies showed that soil microbes such as Metarrhizium anisopliae (Metschn.) Sorok and Trichoderma fungi significantly influenced the aggregation and tunneling preferences of subterranean termites (Xiong et al, 2018b;Xiong et al, 2019;Wen et al, 2020). In our study, different microbes may colonize wooden cylinders or baiting containers containing each clay material and soil, and affect termites' choice.…”
Section: Discussionmentioning
confidence: 64%
“…In addition, previous studies showed that soil microbes such as Metarrhizium anisopliae (Metschn.) Sorok and Trichoderma fungi significantly influenced the aggregation and tunneling preferences of subterranean termites (Xiong et al, 2018b;Xiong et al, 2019;Wen et al, 2020). In our study, different microbes may colonize wooden cylinders or baiting containers containing each clay material and soil, and affect termites' choice.…”
Section: Discussionmentioning
confidence: 64%
“…Likewise in mycoparasitism, the interaction of Trichoderma with insects may be associated with production of bioactive secondary metabolites having insecticidal effect 55 or semiochemical activity, thus influencing insect behavior such as oviposition, 56 choice of host plant [38][39][40] or aggregation. 57 These compounds may possibly act synergistically with extracellular enzymes, such as chitinases, proteases and lipases in the course of entomoparasitic and entomopathogenic activities of Trichoderma.…”
Section: Discussionmentioning
confidence: 99%
“…may act directly through parasitism and entomopathogenic activities, or indirectly by physiological interactions with the plant, which result in the induction of systemic plant defensive responses or attraction of natural enemies or the pest. Likewise in mycoparasitism, the interaction of Trichoderma with insects may be associated with production of bioactive secondary metabolites having insecticidal effect 55 or semiochemical activity, thus influencing insect behavior such as oviposition, 56 choice of host plant 38–40 or aggregation 57 . These compounds may possibly act synergistically with extracellular enzymes, such as chitinases, proteases and lipases in the course of entomoparasitic and entomopathogenic activities of Trichoderma .…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed to investigate whether Trichoderma conidia in soil trigger the aggregation preference by termites. Protocols provided by Xiong et al (2018Xiong et al ( , 2019 were modified to prepare the bioassay arenas. In brief, blocks (40 × 40 × 10 mm [L by W by H]) of soil (sandy clay loam) were made using a plastic mold.…”
Section: Do Trichoderma Species Attractmentioning
confidence: 99%
“…This study aimed to investigate whether Trichoderma conidia in sand trigger the tunneling preference by termites. Methods provided by Xiong et al (2018Xiong et al ( , 2019 were modified to prepare the experiments. The bioassay arenas consisted of two square acrylic plates (156 × 156 × 3 mm [L by W by H]), which were assembled with four narrow edge strips (156/150 × 3 × 1.5 mm [L by W by H]) to create a two-dimensional tunneling chamber.…”
Section: Tunneling-choice Testmentioning
confidence: 99%